Teungku, Dayah, and Traditional Books: Teungku's Teaching Style at Dayah Miftahul Jannah in West Aceh - Navis, Soviatun; Mulasi, Syibran; Tassia, Fransisca (Al Ulya: Jurnal Pendidikan Islam, 2026)
Dayah plays an important role in preserving Islamic scholarly traditions through the study of classical texts. Students' success in understanding classical texts is greatly influenced by Teungku's teaching style. Previous studies have discussed classical texts, but research on Teungku's teaching in traditional Dayah remains limited, especially at Dayah Miftahul Jannah in West Aceh. The novelty of this research lies in its detailed examination of the Teungku's unique teaching style and in broadening the pedagogical perspective of Islamic education. Thus, this study aims to describe the Teungku's teaching style, the role of classical Islamic texts in traditional learning, and the methods used in the teaching process at Islamic boarding schools. This study uses a qualitative research method with a case study design, employing observation, interviews with Teungku and Dayah administrators, and documentation. The results of this study indicate that the method used by Teungku at Dayah Miftahul Jannah is shurah, which involves reading the book and its translation, then explaining it. This study contributes academically by providing insight into traditional teaching strategies and the development of Islamic education based on turats. Teungku's teaching style is very important for the students' understanding of the turats books.